2017
DOI: 10.3126/jcmc.v7i1.17367
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of hemodialysis patients in selected teaching hospitals of Chitwan

Abstract: The quality of life (QOL) needs to be regularly assessed in hemodialysis patients. Hemodialysis patients suffer from average quality of life and survival. A descriptive research design was used, 96 respondents who had received haemodialysis treatment after completion of 1 month duration of hemodialysis in two different teaching hospital at Bharatpur, Chitwan. Data was collected by using standard tool Short Form-36 version2 through face to face structure interview schedule. The objective of study is to find out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…The mean age of our study population was 46.6 years which was slightly lower as compared to a study from Chitwan, Nepal (Mean age 58 years) whereas it was similar to another study from Kathmandu (Mean age 42 years). 5 The most common cause of ESRD in the current study was Hypertension (44%) followed by Diabetes Mellitus (23%) which was similar to a study done in Nepal. 6 , 7 However, this was different in two studies conducted at Bir hospital, Kathmandu where Chronic GN and Diabetes were major causes of CKD.…”
Section: Discussionsupporting
confidence: 89%
“…The mean age of our study population was 46.6 years which was slightly lower as compared to a study from Chitwan, Nepal (Mean age 58 years) whereas it was similar to another study from Kathmandu (Mean age 42 years). 5 The most common cause of ESRD in the current study was Hypertension (44%) followed by Diabetes Mellitus (23%) which was similar to a study done in Nepal. 6 , 7 However, this was different in two studies conducted at Bir hospital, Kathmandu where Chronic GN and Diabetes were major causes of CKD.…”
Section: Discussionsupporting
confidence: 89%
“…The mean age of study population was 47 years which is similar to the study done by Ghimire S et al 4 In last 7 years ou of pocket expenses have increased by nearly double from NRs. 20000 to 35000 as compared to a study from National Kidney Center, Kathmandu done in 2015 which included similar patient profile.…”
Section: Discussionsupporting
confidence: 84%
“…3 In Nepal, every year approximately 2,600 new cases of CKD developed end stage renal disease patient. 4 ThoughHD is free in Nepal, there are many areas of out-of-pocket expenditure that is occurred by patients. The aim of this was study to look into different categories of expenses done by patients in the Bipanna nagarik free HD program provided by government of Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Nepal [32] also reported that being younger offered a better chance of good QOL than being older. Another study conducted in Nepal [33] reported that older age was associated with poor Health related quality of life (HRQOL).…”
Section: Discussionmentioning
confidence: 99%